2019
DOI: 10.2134/agronj2018.12.0749
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Potassium Fertilizer Rate Verification for a Corn–Wheat–Soybean Rotation System in Tennessee

Abstract: Soil test-based fertilizer recommendations are necessary for profitable farming without adversely affecting the environment. The University of Tennessee (UT) stopped recommending P and K fertilizers in 2008 for soils with high Mehlich-1 P and K levels because they were unprofitable. However, commercial laboratories tend to recommend higher fertilizer rates than UT, despite equivalent soil test results. To address this discrepancy, field trials were conducted from 2009 to 2015 for a corn (Zea mays L.)wheat (Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 48 publications
(79 reference statements)
6
17
0
Order By: Relevance
“…Despite a few random responses of H3A-and Mehlich-1-extractable nutrients to managements, in this study Mehlich-1 showed notably lower measurement variability than H3A (Supplemental Table S1). Regardless, the content of nutrients extracted by both H3A and Mehlich-1 solutions were in accordance with other studies conducted in the region (Bansal et al, 2020;Chu et al, 2019;Singh, Savoy, Yin, Schneider, & Jagadamma, 2019;Zhou, Yin, & Verbree, 2014).…”
Section: Extractable Soil Nutrientssupporting
confidence: 91%
See 1 more Smart Citation
“…Despite a few random responses of H3A-and Mehlich-1-extractable nutrients to managements, in this study Mehlich-1 showed notably lower measurement variability than H3A (Supplemental Table S1). Regardless, the content of nutrients extracted by both H3A and Mehlich-1 solutions were in accordance with other studies conducted in the region (Bansal et al, 2020;Chu et al, 2019;Singh, Savoy, Yin, Schneider, & Jagadamma, 2019;Zhou, Yin, & Verbree, 2014).…”
Section: Extractable Soil Nutrientssupporting
confidence: 91%
“…Mehlich‐1 and Mehlich‐3 solutions are commonly used for extracting nutrients from the soil, based on which fertilizer recommendations are calculated (Savoy, 2013). In Tennessee, where the current study was conducted, Mehlich‐1 is the recommended extractant for nutrient analysis (Bansal et al., 2020; Savoy & Joines, 2009; Singh et al., 2019). Switching to H3A in place of Mehlich‐1 and Mehlich‐3 to comply with HSHT will require extensive calibration and validation research in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Lower R 2 values and lack of significant positive correlation between SOC and crop productivity were also reported in studies by Dijkstra and Cheng (2007), Singh et al. (2019a), van Groenigen et al. (2006).…”
Section: Discussionsupporting
confidence: 67%
“…The categories of soil test P levels (Mehlich‐1) for Tennessee soils are: low (0 to 9 mg kg −1 ), medium (9.5 to 15 mg kg −1 ), high (15.5 to 59.5 mg kg −1 ), and very high (≥ 60 mg kg −1 ) (Duncan, Savoy, & Joines, 2015, Savoy & Joines, 2009). Soil samples were collected each year after the harvest of the crop but before applying fertilizers (Savoy, 2013) and Mehlich‐1 extractable soil P levels were evaluated in response to five P treatments (Table 2) (Singh et al., 2019a). At both sites, P application rates of 29 kg ha −1 and > 59 kg ha −1 maintained soil test P in medium and high category respectively (Duncan et al., 2015; Savoy & Joines, 2009; Singh et al., 2019a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation